Influence of personality traits of husband / father on family upbringing - Tetiana Strutynska (Vasyl Stefanyk Precarpathian National University, 2018)
The theoretical principles of the father's family influence on the formation of the male's (father's) features and father's behavior examples are analyzed in this article. Key words: the structure of the family relationships; father's family; father's (husband's) characteristics; parents' influence on the formation of the personality of the husband and wife; parenthood; father's behavior; the formation of a family model based on the parents' family model.